Purification and Characterization of Factor VII Inhibitor Found in a Patient with Life Threatening Bleeding - Kamikubo, Yu-ichi; Miyamoto, Seiji; Iwasa, Atsushi; Ishii, Masao; Okajima, Kenji (Thrombosis and Haemostasis, 2000)
We recently observed a patient with acquired inhibitor-induced F.VII deficiency whose plasma level of F.VII was < 1.0%. However, the biochemical nature of the inhibitor has not yet been clarified. In the present study, we purified the F.VII inhibitor from the patient’s plasma by using activated F.VII (F.VIIa)-conjugated gel and characterized the inhibitor. The results showed that the inhibitor comprised two kinds of antibodies: one was eluted with EDTA (antibody 1) and the other with glycine-HCl buffer (pH 2.3) (antibody 2) from the F.VIIa affinity gel. SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and immunoblotting analysis of these inhibitors demonstrated that both antibodies had features of immunoglobulin G1 (IgG1) with κ and λ-light chains. Antibody 1 bound to the immobilized F.VIIa with a high affinity in the presence of calcium ion, while antibody 2 bound to the F.VIIa very weakly and the binding was independent of calcium ion. Immunoblotting analysis demonstrated that antibody 1 bound to the light chain of F.VIIa after reduction with 2-mercaptoethanol, while it did not react with either the γ carboxyglutamic acid (Gla)-domainless light chain of F.VIIa or the heavy chain with the protease domain. Antibody 1 markedly inhibited the activity of tissue factor-F.VIIa complex. Based on these observations, it is suggested that F.VIIa autoantibody (antibody 1) recognizes the calcium-dependent conformation within or near the Gla domain and inhibits F.VIIa activity by interacting with the light chain.
Keywords: Factor VII(a); autoantibody; Gla domain